The Future of Concluding Governmental Contracts in Light of the Smart Contracts “An Applied Analytical Study in Light of the Block Chain Technology and Digital Currencies” - El-Manaseer , Dr. Suhaib Ahmad Eid (The journal of contemporary issues in business and government, 2021)
The current study is summarized in showing the future of governmental contracts in light of the novelties of the technical and technological revolution, where the smart applications became of its most important. We dealt with this study through two requirements; the first requirement dealt with the essence of smart governmental contracts through four branches. In the first branch we dealt with the concept of smart governmental contracts, in the second branch we talked about the types of smart governmental contracts , in the third branch we displayed the characteristics of smart governmental contracts and finally in the fourth branch we dealt with the legal nature of smart governmental contracts . The second requirement was allocated to talk about the possibility of concluding governmental contracts through smart contracts as a future vision by dividing it into three branches; the first branch was allocated to highlight the essence of smart mediator of agent, the second branch was allocated to set a perspective of the smart governmental tender leading to smart governmental bidding in the third branch, and finally the conclusion which included the main result the study found and the most important recommendations.